Human papillomavirus prevalence and risk factors among Australian women 9–12 years after vaccine program introduction. Issue 34 (9th August 2021) - Shilling, Hannah; Garland, Suzanne M.; Atchison, Steph; Cornall, Alyssa M.; Brotherton, Julia M.L.; Bateson, Deborah; McNamee, Kathleen; Kaldor, John M.; Hocking, Jane S.; Chen, Marcus Y.; Fairley, Christopher K.; McNulty, Anna; et al.
Highlights: A wide range of HPV types were commonly detected among 18–35 year old women. Prevalence of HPV6/11/16/18 was very low and influenced by vaccination status only. Prevalence of non-vaccine types was influenced by known risk factors for infection. Vaccinated women are benefiting from cross-protection against HPV types 31/33/45. HPV vaccination has changed the epidemiology of HPV infection in Australian women. Abstract: Background: In Australia, high and widespread uptake of the quadrivalent human papillomavirus (HPV) vaccine has led to substantial population-level reductions in the prevalence of quadrivalent vaccine targeted HPV genotypes 6/11/16/18 in women aged ≤ 35 years. We assessed risk factors for HPV detection among 18–35 year old women, 9–12 years after vaccine program introduction. Methods: Women attending health services between 2015 and 2018 provided a self-collected vaginal specimen for HPV genotyping (Roche Linear Array) and completed a questionnaire. HPV vaccination status was validated against the National Register. Adjusted odds ratios (aORs) and 95% confidence intervals (CI) were calculated for factors associated with HPV detection. Results: Among 1564 women (median age 24 years; IQR 21–27 years), Register-confirmed ≥ 1-dose vaccine coverage was highest at 69.3% and 68.1% among women aged 18–21 and 22–24 years respectively, decreasing to 42.9% among those aged 30–35 years. Overall prevalence of quadrivalent vaccine-targeted HPV types was very low (2.0%; 95% CI: 1.4–2.8%) and influenced only by vaccination status (5.5% among unvaccinated compared with 0.7% among vaccinated women; aOR = 0.13 (95% CI: 0.05–0.30)). Prevalence of remaining HPV types, at 40.4% (95% CI: 38.0–42.9%), was influenced by established risk factors for HPV infection; younger age-group (p-trend < 0.001), more recent (p < 0.001) and lifetime sexual partners (p-trend < 0.001), but not vaccination status. Prevalence of HPV31/33/45, which shared risk factors with that of non-vaccine targeted HPV types, was also lower among vaccinated (4%) compared with unvaccinated (7%) women (aOR = 0.51; 95% CI: 0.29–0.89), indicative of cross-protection. Conclusion: Vaccination has changed the epidemiology of HPV infection in Australian women, having markedly reduced the prevalence of vaccine-targeted types, including amongst women with known risk factors for infection. Vaccinated women appear to be benefiting from modest cross-protection against types 31/33/45 afforded by the quadrivalent HPV vaccine. These results reinforce the importance of HPV vaccination.